The method of early Advaita Vedanta a study of Gaudapada, Sankara, Suresvara, and Padmapada - Comans, Michael (Delhi Motilal Banarsidass Publishers, 2000)
Study on the teachings of four great propounders of Advaita philosophy.
Keywords: Gaudapada Acarya; Advaita; Vedanta